Complexity in Biological and Physical Systems - Bifurcations, Solitons and Fractals 2018
DOI: 10.5772/intechopen.70870
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle Scattering from Mass and Surface Fractals

Abstract: The concepts of mass and surface fractals are introduced, and the corresponding smallangle scattering (SAS; X-rays, neutrons) intensities are computed. It is shown how to resolve the fractal structure of various complex systems from experimental scattering measurements, and how obtained data are related to specific features of the fractal models. We present and discuss various mass and surface fractal structures, including fractals generated from iterated function systems and cellular automata. In addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…Therefore, the amylopectin network is suspected of having a correlation length of 180 nm (the green triangle toward the right of Figure 10c ). This length is similar to that observed in a 2D SG (Anitas, 2018 ). These correlation lengths can potentially be assigned to the 2D diffusion‐limited clusters.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, the amylopectin network is suspected of having a correlation length of 180 nm (the green triangle toward the right of Figure 10c ). This length is similar to that observed in a 2D SG (Anitas, 2018 ). These correlation lengths can potentially be assigned to the 2D diffusion‐limited clusters.…”
Section: Resultssupporting
confidence: 87%
“…The k ‐value obtained by us agrees well with the analytical value obtained by Muthukumar ( 1983 ) using the mean‐field theory for diffusion‐limited cluster formation. Furthermore, Anita studied the scattering curves from mass and surface fractals in a 2D Sierpinski Gasket (SG), a diffusion‐limited cluster (Anitas, 2018 ). The k ‐value calculated in this case is 1.59, which is comparable to the value obtained by us for a transparent gel.…”
Section: Resultsmentioning
confidence: 99%
“…This widely used material-morphology investigation method has the advantage of sampling a statistically significant macroscopic volume. For ESS structures, the main advantage of SAS relies on its ability to distinguish between mass and surface fractals through the value of the scattering exponent τ in the fractal region [28][29][30][31]. More recently, it has been shown that SAS can also differentiate between ESS and statistically self-similar (SSS) structures [32] as well as between regular and fat fractals, that is, those with positive Lebesgue measure [33].…”
Section: Introductionmentioning
confidence: 99%
“…Note that since all the triangles composing the ST have the same size, the structure is a mass fractal. Therefore, the scattering exponent in the scattering curve shall coincide with the the analytical value of fractal dimension given by Equation (17) (see also [23,26,27]).…”
Section: St Modelmentioning
confidence: 82%